Chemical characterization of milk oligosaccharides of the common wombat (Vombatus ursinus). (26th November 2015) - Hirayama, Kentaro; Taufik, Epi; Kikuchi, Megumi; Nakamura, Tadashi; Fukuda, Kenji; Saito, Tadao; Newgrain, Keith; Green, Brian; Messer, Michael; Urashima, Tadasu
Abstract: Previous structural characterizations of marsupial milk oligosaccharides have been performed in the tammar wallaby, red kangaroo, koala, common brushtail possum and the eastern quoll. To clarify the homology and heterogeneity of milk oligosaccharides among marsupial species, which could provide information on their evolution, the oligosaccharides of wombat milk carbohydrate were characterized in this study. Neutral and acidic oligosaccharides were isolated from the carbohydrate fractions of two samples of milk of the common wombat and characterized by 1 H‐nuclear magnetic resonance spectroscopy. The structures of six neutral saccharides were found to be Gal(β1‐4)Glc (lactose), Gal(β1‐3)Gal(β1‐4)Glc (3'‐galactosyllactose), Gal(β1‐3)Gal(β1‐3)Gal(β1‐4)Glc (3', 3"‐digalactosyllactose), Gal(β1‐3)Gal(β1‐3)Gal(β1‐3)Gal(β1‐4)Glc, Gal(β1‐3)Gal(β1‐3)[Gal(β1‐4)GlcNAc(β1‐6)]Gal(β1‐4)Glc (galactosyl lacto‐N‐novopentaose I) and Gal(β1‐3)[Gal(β1‐4)GlcNAc(β1‐6)]Gal(β1‐3)[Gal(β1‐4)GlcNAc(β1‐6)]Gal(β1‐4)Glc (lacto‐N‐novooctaose), while those of six acidic saccharides were Neu5Ac(α2‐3)Gal(β1‐3)Gal(β1‐4)Glc. (sialyl 3'‐galactosyllactose), Neu5Ac(α2‐3)Gal(β1‐3)Gal(β1‐3)Gal(β1‐4)Glc (sialyl 3', 3"‐digalactosyllactose), Neu5Ac(α2‐3)Gal(β1‐3)[Gal(β1‐4)GlcNAc(β1‐6)]Gal(β1‐4)Glc (sialyl lacto‐N‐novopentaose a), Gal(β1‐3)[Neu5Ac(α2‐3)Gal(β1‐4)GlcNAc(β1‐6)]Gal(β1‐4)Glc (sialyl lacto‐N‐novopentaose c), Neu5Ac(α2‐3)Gal(β1‐3)Gal(β1‐3)Gal(β1‐3)Gal(β1‐4)Glc, , Neu5Ac(α2‐3)Gal(β1‐3)Gal(β1‐3)[Gal(β1‐4)GlcNAc(β1‐6)]Gal(β1‐4)Glc and Gal(β1‐3)Gal(β1‐3)[Neu5Ac(α2‐3)Gal(β1‐4)GlcNAc(β1‐6)]Gal(β1‐4)Glc. In addition, small amounts of sulfated oligosaccharides but no oligosaccharides containing Neu5Gc or α(2–6) linked Neu5Ac were detected.